Identification and characterization of a multispecific monoclonal antibody G2 against chicken prion protein. (14th June 2014) - Kamatari, Yuji O.; Ohta, Shinri; Inoshima, Yasuo; Oda, Masayuki; Maruno, Takahiro; Kobayashi, Yuji; Ishiguro, Naotaka
Abstract We previously generated a monoclonal antibody (mAb), G2, by immunizing mice with Residues 174–247 of the chicken prion protein (ChPrPC). In this study, we found that G2 possessed an extremely unusual characteristic for a mAb; in particular, it could react with at least three proteins other than ChPrPC, the original antigenic protein. We immunoscreened a complementary DNA library from chicken brain DNA and found three proteins (SEPT3, ATP6V1C1, and C6H10orf76) that reacts with G2. There were no regions of amino acid sequence similarity between ChPrPC and SEPT3, ATP6V1C1, or C6H10orf76. We selected ATP6V1C1 as a representative of the three proteins and identified the epitope within ATP6V1C1 that reacts with G2. The amino acid sequence of the G2 epitope within ATP6V1C1 (Pep8) was not related to the G2 epitope within ChPrPC (Pep18mer). However, enzyme‐linked immunosorbent assay, surface plasmon resonance (SPR), and isothermal titration calorimetry (ITC) experiments indicated that these two peptides have similar binding affinity for G2. The apparent KD values of Pep18mer and Pep8 obtained from SPR experiments were 2.9 × 10−8 and 1.6 × 10−8M, respectively. Antibody inhibition test using each peptide indicated that the binding sites of the two different peptides overlapped each other. We observed that these two peptides substantially differed in several binding characteristics. Based on the SPR experiments, the association and dissociation rate constants of Pep18mer were higher than those of Pep8. A clear difference was also observed in ITC experiments. These differences may be explained by G2 adopting different binding conformations and undergoing different binding pathways.